From shoeboxes to shared spaces: participatory cultural heritage via digital platforms. Issue 9 (4th July 2022) - Liew, Chern Li; Goulding, Anne; Nichol, Max
ABSTRACT: Moves towards a post-custodial, participatory paradigm have been well-documented in the cultural heritage sector. The capacity for individuals to contribute to community archives is significant, given their emphasis on representing the experiences of those hidden, ignored, underrepresented or misrepresented by mainstream cultural heritage institutions. Digital platforms offer affordances that can be utilised to encourage the collecting, curating and sharing of collective memories. While there are analyses of individual projects in using technologies for these aims, collective analyses of such practices remain scant in the scholarly literature. This research examines a purposefully selected sample of projects that feature participatory cultural heritage practices and offers a collective analysis of their objectives and motivations, the varying levels of engagement, the technology-mediated participatory activities supported, and how the projects are resourced and sustained. The findings indicate that the enabling of participation through digital platforms vary in nature, depth and extent, and a spectrum approach can be a useful way of conceptualising and envisaging the various levels of engagement in participatory cultural heritage. The collective analysis shows that when projects are designed with a human-centred computing focus and a community-oriented foundation, there is evidence of deeper engagement and sustained participation.